Bloom of Trichogloeopsis pedicellata (Rhodophyta, Nemaliales) following hurricane Iota in San Andrés, Southwestern Caribbean Sea - Gavio, Brigitte; Prato, Julián; Gnecco, Mariana; Maya, María Fernanda; Mancera-Pineda, José Ernesto (Frontiers in Marine Science, 2022)
Hurricanes and tropical storms are a major climatic disturbance with potentially catastrophic effects on costal and marine ecosystems. The impact of these climatic events on coastal communities may vary greatly, and depends on the hurricane’s severity, trajectory and duration. Furthermore, the impact of hurricanes can be patchy, causing extensive damage at some locations, while leaving subjacent others intact. In coral reef areas, breakage, dislodgement, and sand blasting may cause extensive coral mortality, and loss of coral cover may increase due to sedimentation and freshwater run-off. After the impact of the climatic event, successional stages in the reef community have been observed, where blooms of ephemeral algae may occupy space made available by the storm impact. We report a bloom of the red alga Trichogloeopsis pedicellata on the west coast of San Andrés Island, following hurricane Iota. The survey was carried out on seven locations at different depths: shallow (2-5 m) and deep (8-15 m). Three videotransects were recorded at each sampling site, and 15 photo quadrats were analyzed for benthic cover. For biomass estimate, three to five quadrats of 25x25 cm were lied on the substrate, all the alga lying inside was collected and its wet weight determined. Algal cover reached 100% at some locations, with wet biomass up to 5264 g/m2, and persisted several weeks. The bloom was more severe at shallow depth. Apparently, the availability of the substrate due to the detachment of foliose algae triggered the bloom. After a couple of months, the bloom receded naturally.